BS IEC 61156-11. Multicore and symmetrical pair/quad cables for digital communications. Part 11. Symmetrical single pair cables with transmission characteristics up to 600 MHz. Horizontal floor wiring. Sectional specification (9th April 2021) - British Standards Institution,
No abstract available